Associations Between Baseline and Longitudinal Semiautomated Quantitative Joint Space Width at the Hip and Incident Hip Osteoarthritis: Data From a Community‐Based Cohort. Issue 12 (23rd August 2022) - Nelson, Amanda E.; Smith, Jacquelyn A.; Alvarez, Carolina; Arbeeva, Liubov; Renner, Jordan B.; Murphy, Louise B.; Jordan, Joanne M.; Golightly, Yvonne M.; Duryea, Jeffrey
Abstract : Objective: To evaluate quantitative joint space width (JSW) at 10‐, 30‐, and 50‐degree locations in relation to incident radiographic and symptomatic hip osteoarthritis (HOA) in a community‐based cohort. Methods: Data were from Johnston County OA Project participants with supine hip radiographs at each of 4 time points; all had Kellgren/Lawrence (K/L) grades and quantitative JSW. We assessed covariates (age, race, height, weight, body mass index [BMI]) associated with quantitative JSW and hip‐level associations between quantitative JSW and HOA over time using sex‐stratified and multivariable‐adjusted linear mixed models. A cluster analysis with logistic regression estimated associations between quantitative JSW trajectory groups and incident radiographic HOA and symptomatic HOA. Results: At baseline, 397 participants (784 hips, 41% men, 24% Black, mean age 57 years) had a mean BMI of 29 kg/m 2 . Over a mean of 18 years, 20% and 12% developed incident K/L grade–defined radiographic HOA or symptomatic HOA, respectively. Quantitative JSW was more sensitive to changes over time at 50 degrees. Values were stable among men but declined over time in women. Heavier women lost more quantitative JSW; changes in quantitative JSW were not significantly associated with race, education, or injury in women or men. In women only, loss of quantitative JSW over time was associated with 2–3 times higher odds of radiographic HOA and symptomatic HOA; among women and men, narrower baseline quantitative JSW was associated with these outcomes. Conclusion: Hip quantitative JSW demonstrates marked differences in respect to sex, with significant loss over time only in women. Loss of quantitative JSW over time in women and narrower baseline quantitative JSW in men and women were associated with incident radiographic HOA and symptomatic HOA.